2012
DOI: 10.1126/science.1224514
|View full text |Cite
|
Sign up to set email alerts
|

Tissint Martian Meteorite: A Fresh Look at the Interior, Surface, and Atmosphere of Mars

Abstract: Tissint (Morocco) is the fifth martian meteorite collected after it was witnessed falling to Earth. Our integrated mineralogical, petrological, and geochemical study shows that it is a depleted picritic shergottite similar to EETA79001A. Highly magnesian olivine and abundant glass containing martian atmosphere are present in Tissint. Refractory trace element, sulfur, and fluorine data for the matrix and glass veins in the meteorite indicate the presence of a martian surface component. Thus, the influence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
111
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 32 publications
23
111
1
1
Order By: Relevance
“…The mineralogy and petrography of Tissint resemble other olivine-phyric shergottites (details in the Supplementary Information) and other pieces of the same fall 5,6 . Detailed mineralogy and petrography of Tissint from our study will be reported elsewhere, but a brief summary is given in the Supplementary Information.…”
Section: Mineralogymentioning
confidence: 83%
“…The mineralogy and petrography of Tissint resemble other olivine-phyric shergottites (details in the Supplementary Information) and other pieces of the same fall 5,6 . Detailed mineralogy and petrography of Tissint from our study will be reported elsewhere, but a brief summary is given in the Supplementary Information.…”
Section: Mineralogymentioning
confidence: 83%
“…A sub-aliquot of the recent Tissint fall was isolated containing a visually estimated 40-50% of black glass. The black glass has been suggested to represent a surface component on Mars (Chennaoui Aoudjehane et al, 2012). Additionally, to investigate potential pre-terrestrial alteration processes, a two-step ultrasonic leaching procedure was applied to an aliquot of NWA 817, which contains a large proportion of mesostasis (>15%) and evidence for pervasive pre-terrestrial aqueous alteration (see Gillet et al, 2002), by leaching for 2 Â 10 min in de-ionized water and then for 10 min with 1 M HCl.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Sulfur concentrations of Los Angeles, Zagami, Nakhla and Tissint have been measured in previous studies (Aoudjehane et al, 2012;Banin et al, 1992;Burgess et al, 1989;Franz et al, 2014;Gibson et al, 1985;Dreibus et al, 1982). Sulfur concentrations in Tissint and Zagami from this study agrees well with those from previous studies (Aoudjehane et al, 2012;Gibson et al, 1985). However, bulk S concentrations of Los Angeles and Zagami from this study are both higher than the total S reported in Franz et al (2014).…”
Section: Comparison With Previous Bulk Sulfur Data Of Martian Meteoritesmentioning
confidence: 95%